Investigating the Factors Affecting Women's Political Participation in Nepal: A Qualitative Study - Prabhat Bajimaya (Journal of Public Representative and Society Provision, 2022)
This qualitative study investigates the factors affecting women's political participation in Nepal. The research employed semi-structured interviews with 15 female politicians and 10 male politicians to collect data. The findings indicate that despite constitutional and legal provisions, women's political participation remains low due to various social, cultural, economic, and political factors. Challenges include gender discrimination, lack of education and awareness, patriarchal attitudes and beliefs, cultural norms and traditions, poverty, and political violence. The study emphasizes the need for policy and program interventions that promote gender equality and women's empowerment to enhance women's political participation. The involvement of various stakeholders, including civil society organizations, political parties, government agencies, and the media, is crucial for sustainable progress.